Profil Program Fisioterapi pada Pasien Stroke Berdasarkan NIHSS di Rawat Inap RSUD Dr. Saiful Anwar Malang pada Januari-Maret 2023 - Izzati, Fatma; Setianto, Catur (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Introduction: Stroke is one of the highest causes of disability in the world. Indonesia already has guidelines for stroke rehabilitation, but the implementation of these guidelines in hospitals in Indonesia is rarely studied. Purpose: This study aims to determine the profile of the physiotherapy program in post-acute phase stroke patients who are hospitalized at Dr. Saiful Anwar General Hospital Malang in January-March 2023 based on the National Institutes of Health Stroke Scale (NIHSS). Methods: The study was conducted using a descriptive-quantitative method. Data taken from the electronic medical records of Dr. Saiful Anwar Malang in January-March 2023. Results: There were 129 stroke patients who met the inclusion criteria consisting of 56.6% men and 43.4% women, with the most age range being 51-60 years (34.88%). The highest stroke severity was severe stroke (NIHSS 21-42) as much as 34.88%, then moderate stroke (NIHSS 5-15) as much as 31.01%, moderate-severe stroke (NIHSS 16-20) 19.38%, and mild stroke (NIHSS 1-4) 14.73%. Almost all patients in all levels of severity received proper positioning, gradual mobilization, and chest physical therapy (the smallest percentage was 73.68% in mild stroke). Apart from these three interventions, for mild stroke, the most rehabilitation intervention given was AAROM exercise (57.89%), for moderate stroke was AROM exercise (62.5%), for moderate-severe stroke was PROM exercise (72%) , in severe stroke is PROM exercise. Conclusion: All stroke patients at all severity levels receive proper positioning, gradual mobilization, and chest physical rehabilitation, but motor, sensory, cognitive, and other physioteherapy programs for patients differ depending on the severity.